1993
DOI: 10.1093/nar/21.8.1747
|View full text |Cite
|
Sign up to set email alerts
|

Cloning and characterization of a naturally occurring antisense RNA to human thymidylate synthase mRNA

Abstract: Based upon reverse transcription and polymerase chain reaction results with human KB cell RNA, a cDNA (i.e., 3'rTS1, 1557 nt) with complementarity to thymidylate synthase mRNA was cloned and sequenced. Northern blot analysis showed that 3'rTS1 corresponded to a cytoplasmic 1.8 kb RNA found in several tumor cell lines. The remaining 5' region of this antisense RNA was cloned by a RACE (Rapid Amplification of cDNA Ends) procedure. A full length cDNA (i.e., rTS, 1811 nt) was generated by splicing 3'rTS1 with RACE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
41
0

Year Published

1994
1994
2012
2012

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(41 citation statements)
references
References 10 publications
0
41
0
Order By: Relevance
“…These results, however, did not fulfill the expected enzyme function. On the other hand, when considered together with clinical outcomes, our work suggested that the nuclear level of rTSß may not only be associated with increased 5-FU resistance, but also with a higher incidence of lymph node involvement, ER and/or PR expression, Her2-neu gene amplification and advanced tumor stage, events that are intimately associated with the rapid growth of breast cancer cells (14)(15)(16), and that rTSß may act as a nucleus-housed glycolytic protein, which may play a role during G2/M phases of cell cycle progression.…”
Section: Discussionmentioning
confidence: 84%
See 3 more Smart Citations
“…These results, however, did not fulfill the expected enzyme function. On the other hand, when considered together with clinical outcomes, our work suggested that the nuclear level of rTSß may not only be associated with increased 5-FU resistance, but also with a higher incidence of lymph node involvement, ER and/or PR expression, Her2-neu gene amplification and advanced tumor stage, events that are intimately associated with the rapid growth of breast cancer cells (14)(15)(16), and that rTSß may act as a nucleus-housed glycolytic protein, which may play a role during G2/M phases of cell cycle progression.…”
Section: Discussionmentioning
confidence: 84%
“…Treatment with manumycin A, on the other hand, decreased expression and nuclear translocation of rTSß. The addition of manumycin A also inhibits the protein level of TS and α-tubulin, and such results suggest that farnesylation of rTSß could prevent protein degradation and maintain protein level in the cells (14)(15)(16). Moreover, our data indicated that like fatty acyl modification of the G-proteins, which help in determining the final destination of the protein either to the plasma membrane or to the endoplasmic reticulum to carry out the respective biological functions (32), farnesylation could also help in determining the organelle targeting of rTSß.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…In higher animals, including humans, antisense genes only seem to exist as fragments, and they lack some of the features shared by normal (sense) genes. At least one such antisense gene fragment is expressed in the brain (Adelman et al 1987;Takayama & Inouye, 1990;Dolnick, 1993). In addition, there are genes that have a sequence complementary to a sense gene, or part of it, but which are encoded at a different site in the genome; they, therefore, cannot be called true antisense genes, but their sequence complementarity suggests they have antisense-like effects.…”
mentioning
confidence: 99%